MODEL PEMBELAJARAN MOTORIK YANG MENYENANGKAN DI PENDIDIKAN ANAK USIA DINI - Yudha Febrianta (Universitas Sarjanawiyata Tamansiswa, 2017)
At this age motor development of children can be developed properly, the child’s motor can be a stimulus with a wide range of models, the motor development was developed early on because it will affect the growing kembanganya later, then to train the child’s motor, both gross motor and fine motor perleu do stimulus with existing models of motor learning. To develop the motor skills of children, teachers can use different models of motor learning, early childhood, the model was used to reach the children’s learning. Education in schools for early childhood has its own characteristics so that the motor learning models used should be selected according to early childhood. In motor learning model selection is done in order to ensure the child is not injured, the child feels uncomfortable, fearful or anxious in doing these movements.